Breeding Potency And History Of Selected Animal Species in Jos Wildlfe Park (2006)
Anthropogenic activities have decimating implications on widlife population in the ecosystem. Breeding of wild animals in captivity was introduced as a way to safe species from extinction but this has posed some challenges. The study surveyed the breeding potency, trend, history and infant mortality of selected animal species in Jos Wildlife Park. Data for toe study were obtained through oral interviews, observations, review of records and structured questionnaires. 24 respondents were randomly sampled. Data obtained were analysed using descriptive statistics in form of tables, percentages and frequency of counts. Results revealed that lion, Panthera leo (Linnaeus, 1758); leopard, Pantoera pardus(Unnaeus, 1758); pigmy hippopotamus, Choeropsis liberiensis (Morton, 1849); derby eland, Taurotragus derbianus (Gray, 1847); stripped hyaena, Hyaena hyaena(Linnaeus, 1758); Grimms duiker (Syhacapra grimmiaiinnaeus, 1758); Red-flanked duiker, CephaJophus rufilatus (Gray, 1846); and MaxwelFs duiker Cephatophus maxweffi (Smith, 1827); and Kob Kobus kob (Erxleben, 1777); Waterbuck, Kobus ellipsiprymnus (OgBby, 1833); and Red-fronted; gazelle, Gazella rufifrons (Gray, 1846) procured from different places have produced 17; 10; 8; 13; 24; 1; 6; 2; and 4 number of individuals respectively since inception of the park. The breeding of carnivores was between the years 1979 and 1993 with three infant mortalities. The pigmy hippopotamus, Choeropsis liberiensis bred between the years 1980 to 1992 with one infant mortality. The herbivores have been breeding almost on yearly basis with no infant mortality. Two leopards procured from the University of Ibadan did not breed. The only infant mortality recorded by toe leopard was due to cannibalism. Jos W iife Park has been breeefing, nurturing and distributing endangered, threatened, rare and abundant species of w M fe to several conservation centres in Nigeria suggestions to improve breeding of animal species were made.